Revitalisasi Tata Kelola menuju Bumdes Produktif pada Bumdes Tanjung Siput Ohoi Lairngangas di Kabupaten Maluku Tenggara: Governance Revitalization towards Productive Bumdes in Bumdes Tanjung Siput Ohoi Lairngangas in Southeast Maluku Regency - Lewaherilla, Novalien Carolina; Ralahallo, Fransiska Natalia; Loppies, Lilian Sonya (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
The purpose of implementing this PKM activity is to provide understanding and knowledge about productive BUMDes management, due to the phenomenon that occurred in Tanjung Siput BUMDes Ohoi Lairngangas in Southeast Maluku Regency and to encourage the creation of competitive BUMDes governance in accordance with the nature of its presence, namely to improve the economic welfare of rural communities. Through the Participatory Action Research (PAR) method to the Management and Members of BUMDes, the process of sharing knowledge and skills is carried out, among others regarding the bookkeeping system and its application to BUMDes, Financial Management Implementation, strategies for handling non-performing loans through credit analysis training and strengthening organizational governance through organizational training. The conclusion of this PKM activity is that the understanding of BUMDes members in the field of production management and marketing can increase and there is a change in the mindset of BUMDES members to be more professional and able to run BUMDes.